Lifestyle and heritability effects on cancer in Bangladesh: an application of Cox proportional hazards model (Asian Journal of Medical and Biological Research, 2021)
The burden of cancer is increasing very rapidly day by day all over the world, largely due to an increasing unhealthy lifestyle. Some cross-sectional studies have been conducted on lifestyle of cancer patients based on Sylhet city, Bangladesh. However, to the best of our knowledge, no study has been done based on longitudinal aspect considering whole Bangladesh, therefore, we aimed to conduct a longitudinal study to know the effects of lifestyle and heritability on cancer in Bangladesh. We selected total 384 cancer patients by using simple random sampling from eight divisions during December 2018, and created a cohort in each division in Bangladesh. After one year, we collected their survival data from four selected cohorts. We used a Cox proportional hazards model for survival data. It was found that overall female patient’s survival rate is higher than male patients. It was also observed that the significant factors of the lifestyle dimension influence the hazard function of the cancer patients. It indicates that more consumption of beverages, fast food, chips/chocolates/ice-cream, smoking and betel nut increased the hazard of cancer. That is, changing lifestyle is needed to reduce the cancer diseases in future. Taken together, the findings of this study may be able to make awareness in the society about the cancer, afterwards it might be able to reduce the cancer diseases in future in regional, national and international level to improve public health sectors.Asian J. Med. Biol. Res. March 2021, 7(1): 82-89